INTERNATIONAL SCIENTIFIC CONFERENCE XXXI KRUPNOV READINGS "ARCHAEOLOGICAL HERITAGE OF THE CAUCASUS: CURRENT PROBLEMS OF STUDY AND CONSERVATION», Makhachkala, October 26-31, 2020 - Gadziev, Murtazali Serazutdinovic; Zilivinskaa, Emma Davidovna; Kulakov, Sergej Aleksandrovic; Savenko, Sergej Nikolaevic; Erlih, Vladimir Roal'dovic (History, Archeology and Ethnography of the Caucasus, 2021)
The article presents information about the International Scientific Conference XXXI Krupnov's readings "Archaeological Heritage of the Caucasus: Topical Problems of Study and Conservation," which was held on October 26-31, 2020 in Makhachkala, Republic of Daghestan. The conference was dedicated to the 50th anniversary of the Krupnov's readings and the 50th anniversary of the Derbent archaeological expedition. The conference was attended by scientists from Moscow, St. Petersburg, Ghent, Grozny, Maykop, Makhachkala, Nazran, Nalchik, Oxford, Pushchino, Pyatigorsk, Tyumen, Stavropol, Sukhum, Vladikavkaz. At the beginning of the conference, a collection of conference materials was published, which included 141 publications of reports by more than 210 authors. The subject of the reports reflected a wide range of archaeological studies, covering the chronological range from the Stone Age to the Late Middle Ages.
Keywords: Krupnov's readings; archaeology of the Caucasus; archaeological conference; preservation of archaeological heritage